ADVANCEMENTS IN THE TREATMENT OF FEMALE PATIENTS WITH CIN I AND CONFIRMED HPV INFECTION - Mirzaeva Yu.K., Nadyrkhanova N.S. (Central Asian Journal of Medicine, 2025)
Cervical intraepithelial neoplasia grade I (CIN I), in conjunction with the detection of human papillomavirus (HPV), presents a clinical dilemma in reproductive health care—balancing overtreatment against disease progression. This article reviews contemporary approaches to managing women diagnosed with CIN I and confirmed HPV infection, emphasizing personalized care strategies, immunomodulatory therapies, and the role of active surveillance. Evidence-based comparisons of antiviral, ablative, and regenerative treatments are discussed, including their efficacy, recurrence rates, and safety profiles. The paper also highlights molecular diagnostics and genotyping as tools for risk stratification and tailored interventions. This modernized framework supports clinical decision-making that reduces unnecessary procedures while promoting long-term cervical integrity and patient-centered outcomes.